2021
DOI: 10.1136/bmj.n736
|View full text |Cite
|
Sign up to set email alerts
|

The methodological quality of individual participant data meta-analysis on intervention effects: systematic review

Abstract: Objective To assess the methodological quality of individual participant data (IPD) meta-analysis and to identify areas for improvement. Design Systematic review. Data sources Medline, Embase, and Cochrane Database of Systematic Reviews. Eligibility criteria for selecting studies Systematic reviews with IPD meta-analyses of randomised controlled trials on interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Indeed, a recent meta-epidemiological study found that a priori protocols more often are lacking for IPD meta-analyses compared with traditional study-level meta-analyses. 50 Furthermore, risk of bias for the included trials are less commonly assessed according to recommended standards, and only 40% of IPD meta-analyses accounted for risk of bias in any way when interpreting the overall results (See Summarizing the Evidence below). 50…”
Section: Ipd Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent meta-epidemiological study found that a priori protocols more often are lacking for IPD meta-analyses compared with traditional study-level meta-analyses. 50 Furthermore, risk of bias for the included trials are less commonly assessed according to recommended standards, and only 40% of IPD meta-analyses accounted for risk of bias in any way when interpreting the overall results (See Summarizing the Evidence below). 50…”
Section: Ipd Meta-analysismentioning
confidence: 99%
“…50 Furthermore, risk of bias for the included trials are less commonly assessed according to recommended standards, and only 40% of IPD meta-analyses accounted for risk of bias in any way when interpreting the overall results (See Summarizing the Evidence below). 50…”
Section: Ipd Meta-analysismentioning
confidence: 99%
“…Despite the challenges in obtaining, and preparing IPD for MA, a systematic review of 323 IPDMAs across different specialty areas reported that 54% obtained IPD from over 80% of eligible trials, and 87% obtained IPD from over 50% of eligible trials [ 25 ]. The 2021 United Nations Educational, Scientific and Cultural Organisation (UNESCO) Recommendation on Open Science provides strong global support for making scientific knowledge openly available, accessible and reusable [ 26 ].…”
Section: Individual Participant Data Meta-analysismentioning
confidence: 99%
“…It has been highlighted that there are several main types of research data repositories: Institutional, disciplinary, multidisciplinary and project specific [ 10 ]. Availability of raw data in open repositories facilitates the adequate development of meta-analysis, particularly individual patient data -IPD- meta analyses [ 11 ], and the cumulative evaluation of evidence for specific topics [ 12 ], especially for high-dimensional data [ 13 ] (such as results from genomics, transcriptomics or epigenomics). In this context, certain research fields, such as genomics, have developed standards that facilitate and promote deposition of raw data [ 14 ].…”
Section: Main Textmentioning
confidence: 99%